A construção de um controle negociado : o trabalho dos auxiliares de fiscalização da prefeitura de Belo Horizonte - Araújo Filho, Tarcísio Perdigão (2016)
This research aims to understand how the control of practices in public spaces is elaborated, wich is part of the urban surveillance so called "fiscalização" of Belo Horizonte, under the protection of the Código de Posturas (2003). This is a social control which focuses on the regulation of street vendors activities, marked as "social problem" in a context of "urban order" promotion. Further than an analysis that prioritizes organizational or institutional ideal types, this research developed between 2013 and 2015, priorized the data collection "from inside", from an interactional point of view. For this, qualitative research techniques (interviews and observation) were operated in order to keep the subjects working practices as the main reference for descriptions and analyzes. These workers work daily on city streets in direct contact with the street vendors (interacting with other people, like other professional groups) in different part of the fronts of street surveillance: the plantões, the equipes de Apoio and the operações. In general, the practices of these assistants anticipates the participation of their bosses, the fiscais integrados (and other authorities in this field), reducing, as an effect, their workload. At the same time, these assistants actively participate of the situational production of references of differenciation (between formal /informal, bearable/unbearable) and social control as a whole. The research effort was to come up, in an interrelated manner, the various aspects that make up the street surveillance as a social construction. At the beginning, I analysed the strategic and managerial aspects enrolled in practical work of these agents in different working arrangements and enviroments, giving a focus on how the control is produced in a negotiated manner, although it is constantly rationalized as a tool for public space management. The analysis was enlarged by replacing the focus on the continuities and discontinuities between the private life aspects and the work aspects, from the reconstruction of trajectories of some of the research subjects. Through this perspective, it was possible to work out with some different social aspects (such as class and gender) in order to observe and describe the practices that reveal the main basis and senses of this social and relational control. All this conjugated analysis dimensions demonstrate how this particular control is produced. At the same time, it shows, from this field, some modes of circulation of power.